ANALYSIS OF RESULTS OF TREATMENT OF NEWBORNS WITH OMPHALOCELE - Ruzmatov, I.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Evaluation of the results of the nearest and qualified treatment in newborns with omphalocele. Material and methods: Studies were carried out on 103 newborns with Omphalocele (45 girls and 58 boys), who were on treatment in the Republican educational-Medical-methodical center of neonatal surgery. Results: At small and average volume of omphalocele the radical plastic of a front-abdominal wall is recommended, large-the choice depends on a degree of viscero-abdominal imbalance and severity of malformations. The casings of the new surgical intervention increased the number of surviving patients by 1,4 times. “Good” and “satisfactory” results increased in 2,5 and 1,4 times, “unsatisfactory” decreased by 6,1 times. Conclusion: The obtained results allow to recommend wide implementation of the proposed method of operative treatment of Omphalocele.